Evaluación del servicio de atención al usuario en la Dirección Municipal de transporte terrestre, tránsito y seguridad vial del Cantón Bolívar. - Brito Donoso, María Gabriela (2018)
The evaluation of the services provided by the Municipal Directorate of Land Transportation, Traffic and Road Safety of the Bolívar canton, aimed at assessing the perceptions and expectations, for which an interview was conducted with the chief, who provided information on the processes developed in this instance, in addition to those involved, functions, plans and projects, aimed at efficient management with a view to improving the quality and safety of citizens. Subsequently, the construct was designed to carry out user surveys, which through the Licker scale reflected the level of satisfaction of the perceived service, as well as adverse situations, which through a plan of improvements and strategies will allow possible solutions, and will reflect a solid public management, based on the principles of quality, warmth, efficiency and effectiveness.